Changes in colour and mechanical properties of wood polypropylene composites on natural weathering - Gunjal, Jayashri; Aggarwal, Pankaj; Chauhan, Shakti (Maderas. Ciencia y Tecnología, 2020)
This comparative study focused on understanding the effect of coupling agent and particle size on weathering behaviour of wood polypropylene composite. Two coupling agents, namely maleic anhydride grafted polypropylene and m-TMI (m-Isopropenyl-a,a- dimethylbenzyl isocyanate) grafted polypropylene were used in preparation of the composites. The composites were exposed to outdoor conditions for one year and changes in surface colour and mechanical properties were measured after 2, 4, 8 and 12 months of natural weathering. During the initial four months of weathering considerable colour change was observed with increase in lightness. Mechanical properties were unaffected largely for the initial four months and thereafter started declining. Overall, tensile strength decreased by about 15 % and flexural strength decreased by about 8 % after one year of weathering. The flexural modulus also decreased by about 10 %. Wood particle size was found to affect the aesthetic and strength of the composites after natural weathering. Coupling agents had a positive impact on mechanical properties however their influence on weathering degradation was not noticeable.